Corrosion Resistance Study of Electrophoretic Deposited Hydroxyapatite on Stainless Steel for Implant Applications - Chew, Kean-Khoon; Zein, Sharif Hussein Sharif; Ahmad, Abdul Latif; McPhail, David S.; Boccaccini, Aldo R. (Key Engineering Materials, 2012)
Stainless steel (SS) is often used for orthopaedic and dental implants because of its excellent mechanical characteristics. However, from an electrochemical perspective, SS can be susceptible to corrosion-related problems. Inorganic bioactive coatings on SS surfaces are reported to impart corrosion resistance and enhance biocompatibility. In this paper, hydroxyapatite (HA) coatings were developed on SS 316L by an electrophoretic deposition (EPD) technique at applied deposition voltages from 10 to 60 V in an acidic aqueous solution. The present study was performed to optimise the applied voltage required to produce stable HA coatings on SS 316L. Their corrosion resistance in simulated body conditions were investigated using the potentiodynamic polarization curves. The results of the electrochemical studies revealed that the optimal applied voltage for EPD of HA on SS 316L was 40 V. The polarisation parameters, such as the corrosion potential, breakdown potential and repassivation potential of HA coated materials demonstrated nobler behaviours than the uncoated SS 316L. These results validated the successful formation of stable and protective HA coatings on SS 316L. © (2012) Trans Tech Publications, Switzerland.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.corros
Keywords: Corrosion resistance; Electrochemical study; Electrophoretic deposition; Hydroxyapatite; Stainless steel